Equipping community pharmacy workers as agents for health behaviour change: developing and testing a theory-based smoking cessation intervention. Issue 8 (11th August 2017) - Steed, Liz; Sohanpal, Ratna; James, Wai-Yee; Rivas, Carol; Jumbe, Sandra; Chater, Angel; Todd, Adam; Edwards, Elizabeth; Macneil, Virginia; Macfarlane, Fraser; Greenhalgh, Trisha; Griffiths, Chris; et al.
Abstract : Objective: To develop a complex intervention for community pharmacy staff to promote uptake of smoking cessation services and to increase quit rates. Design: Following the Medical Research Council framework, we used a mixed-methods approach to develop, pilot and then refine the intervention. Methods: Phase I : We used information from qualitative studies in pharmacies, systematic literature reviews and the Capability, Opportunity, Motivation—Behaviour framework to inform design of the initial version of the intervention. Phase II : We then tested the acceptability of this intervention with smoking cessation advisers and assessed fidelity using actors who visited pharmacies posing as smokers, in a pilot study. Phase III : We reviewed the content and associated theory underpinning our intervention, taking account of the results of the earlier studies and a realist analysis of published literature. We then confirmed a logic model describing the intended operation of the intervention and used this model to refine the intervention and associated materials. Setting: Eight community pharmacies in three inner east London boroughs. Participants: 12 Stop Smoking Advisers. Intervention: Two, 150 min, skills-based training sessions focused on communication and behaviour change skills with between session practice. Results: The pilot study confirmed acceptability of the intervention and showed preliminary evidence of benefit; however, organisational barriers tended to limit effective operation. The pilot data and realist review pointed to additional use of Diffusion of Innovations Theory to seat the intervention in the wider organisational context. Conclusions: We have developed and refined an intervention to promote smoking cessation services in community pharmacies, which we now plan to evaluate in a randomised controlled trial. Trial registration number: UKCRN ID 18446, Pilot.